Taming the Big Green Elephant Setting in Motion the Transformation Towards Sustainability - Hernández, Ariel Macaspac (Globale Gesellschaft und internationale Beziehungen, 2021)
In this open access publication it is shown, that sustainable low carbon development is a transformative process that constitutes the shifting from the initially chosen or taken pathway to another pathway as goals have been re-visited and revised to enable the system to adapt to changes. However, shifting entails transition costs that are accrued through the effects of lock-ins that have framed decisions and collective actions. The uncertainty about these costs can be overwhelming or even disruptive. This book aims to provide a comprehensive and integrated analytical framework that promotes the understanding of transformation towards sustainability. The analysis of this book is built upon negotiative perspectives to help define, design, and facilitate collective actions in order to execute the principles of sustainability. Dr Dr Ariel Macaspac Hernandez is currently a researcher at the German Development Institute belonging to the research cluster knowledge cooperation and environmental governance. He was/is also a lecturer on negotiations, conflict and resource management, sustainability politics, environmental governance, climate change policies, development aid and sustainable energy systems in various universities in Germany, Philippines, Jamaica, Estonia, Spain and Mexico.